2009
DOI: 10.1007/s10964-009-9433-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Family Connectedness and Body Satisfaction: A Longitudinal Study of Adolescent Girls and Boys

Abstract: The present study examined the longitudinal links between perceptions of family connectedness and body satisfaction in 1,774 (52% female) adolescents. Participants (10-15 years of age at Time 1) completed self-report measures at three measurement occasions separated by 1 year each. Mean group difference results showed that both body satisfaction levels and perceived levels of family connectedness decreased over 2 years for the whole sample. As expected, girls were generally less satisfied with their bodies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 34 publications
6
51
1
3
Order By: Relevance
“…The reverse direction impact of body satisfaction on subsequent family connectedness found among both girls and boys can be understood from a family systems perspective (Minuchin, 1986) whereby experiences of one member of the family impact on the whole family system. Adolescents with high levels of body dissatisfaction may also experience higher levels of depression and less positive social interactions leading to lower family connectedness (Crespo et al, 2010). In summary, this research emphasizes the importance of examining bidirectional or reverse causal relationships in longitudinal data and being sensitive to specific developmental issues in the data set.…”
Section: Developmental Factors Andmentioning
confidence: 89%
See 1 more Smart Citation
“…The reverse direction impact of body satisfaction on subsequent family connectedness found among both girls and boys can be understood from a family systems perspective (Minuchin, 1986) whereby experiences of one member of the family impact on the whole family system. Adolescents with high levels of body dissatisfaction may also experience higher levels of depression and less positive social interactions leading to lower family connectedness (Crespo et al, 2010). In summary, this research emphasizes the importance of examining bidirectional or reverse causal relationships in longitudinal data and being sensitive to specific developmental issues in the data set.…”
Section: Developmental Factors Andmentioning
confidence: 89%
“…Indeed, another study found a bidirectional relationship between body satisfaction and family connectedness among adolescent girls aged 10-15 but a unidirectional relationship for their male counterparts where body dissatisfaction predicted changes in family connectedness across the first year of the study (Crespo, Kielpikowski, Jose, & Pryor, 2010). It is likely that family connectedness provides girls with positive messages about themselves, about their appearance and acceptance of changes in their bodies as they develop through puberty (Crespo et al, 2010). Family connectedness may also provide protection from negative sociocultural appearance pressures for girls (Bearman, Presnell, Martinez, & Running Head: Future Directions 24 Stice, 2006).…”
Section: Developmental Factors Andmentioning
confidence: 98%
“…Indeed, styles of interaction within families have long been hypothesized to influence body image development and eating disorder symptoms (see review Steinberg and Phares 2001). Recent studies have noted characteristics such as hostility, low expressiveness, and lack of cohesion in many families of children and adults with poorer body satisfaction (Crespo et al 2010). Ogden and Steward (2000) posited an ''interactive'' hypothesis whereby specific qualities of the motherdaughter relationship, as opposed to modeling alone, predict daughter's body image.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, each one was ranked at the top by at least one board member. One of the articles was by Crespo et al (2010). Their study explored the longitudinal links between perceptions of family connectedness and body satisfaction in 1,774 (52% female) adolescents and found bidirectional effects between perceptions of family connectedness and body satisfaction for girls, but not for boys.…”
mentioning
confidence: 99%